PERANAN EPIDERMAL GROWTH FACTOR PADA PENYEMBUHAN LUKA PASIEN ULKUS DIABETES - Dinar Erina Destyani Putri; Sriwidodo . (Fakultas Farmasi, Universitas Padjadjaran, 2016)
Increased prevalence of diabetic raises a lot of concomitant diseases like diabetic ulcers. Diabetic ulcers which not treated properly can lead to amputation. Wound healing in patients with diabetic ulcers involves many factors including growth factor. Epidermal growth factor is a growth factor that plays a role in the formation of collagen in wounds. Some applications EGF has been applied to the diabetic ulcer of 1-4 degrees showed significant improvement of diabetic ulcer wounds. Safety studies about EGF also showed irritation was generally mild to moderate.